PENGARUH CITRA PRODUK DAN KUALITAS LAYANAN TERHADAP KEPUASAN DAN DAMPAKNYA TERHADAP LOYALITAS (Studi Pada Pelanggan Mata Dewa Photo Studio Semarang) - Akbar Prayuda, 11.05.51.0103 (Students Journal of Economic and Management, 2015)
Conditions of intense competition makes consumers extremely vulnerable to change, so that every company seeks to attract customers and maintain customer relationships. This study aims to transform and analyze the effect of product image and quality of service to customer satisfaction and loyalty in the Mata Dewa Photo Studio Semarang. In this study, researchers used population of all buyers and consumers Mata Dewa Photo Studio Semarang. The method used is purposive sampling method. The samples used were 100 buyers and consumers Mata Dewa Photo Studio Semarang. Test equipment in this study using multiple linear regression, and Sobel Test. Results of this study are the product image positive effect on customer satisfaction, service quality has positive influence on customer satisfaction, product image positive effect on customer loyalty, service quality has positive effect on customer loyalty and customer satisfaction has positive influence on customer loyalty. Customer satisfaction mediates the effect of quality of service and product image on customer loyalty. Keywords: image of a product, service quality, satisfaction, loyalty